Heart Failure with Recovered Ejection Fraction: Clinical Description, Biomarkers, and Outcomes - Basuray, Anupam (2014)
BACKGROUND: We hypothesized that heart failure (HF) patients who recover left ventricular function (HF-Recovered) have a distinct clinical phenotype, biology and prognosis compared to HF with reduced ejection fraction (HF-REF) and HF with preserved ejection fraction (HF-PEF). METHODS AND RESULTS: The Penn Heart Failure Study (PHFS) is a prospective cohort of 1,821 chronic HF patients recruited from tertiary HF clinics. Participants were divided into three categories based on echocardiograms: HF-REF if EF<50%, HF-PEF if EF consistently ≥50%, and HF-Recovered if EF on enrollment to PHFS was ≥50% but prior EF<50%. A significant portion of HF-Recovered patients had an abnormal biomarker profile at baseline, including 44% with detectable Troponin I, although in comparison, median levels of BNP, sFlt-1, Troponin I and creatinine were greater in HF-REF and HF-PEF patients. In unadjusted Cox models over a maximum follow-up of 8.9 years, the hazard ratio (HR) for death, transplant or ventricular assist device in HF-REF was 4.1 (95%CI 2.4–6.8; p<0.001) and in HF-PEF was 2.3 (95%CI 1.2–4.5; p=0.013), as compared to HF-Recovered. The unadjusted HR for cardiac hospitalization in HF-REF was 2.0 (95%CI 1.5–2.7; p<0.001) and in HF-PEF was 1.3 (95%CI 0.90–2.0; p=0.15), compared to HF-Recovered. Results were similar in adjusted models. CONCLUSIONS: HF-Recovered is associated with a better biomarker profile and event-free survival than HF-REF and HF-PEF. However, these patients still have abnormalities in biomarkers and experience a significant number of HF hospitalizations, suggesting persistent HF risk.